Associations Between Target Lesion Restenosis and Drug-Eluting Balloon Use: An Observational Study. Issue 3 (January 2016) - Lee, Wei-Chieh; Wu, Chiung-Jen; Chen, Yung-Lung; Chung, Wen-Jung; Hsueh, Shu-Kai; Hang, Chi-Ling; Fang, Chih-Yuan; Fang, Hsiu-Yu
Abstract : Abstract: Percutaneous coronary interventions (PCIs) with drug-eluting balloons (DEBs) have emerged as an adjunctive treatment for in-stent restenosis (ISR) lesions. However, recurrent restenosis still occurs following DEB use. Our study aimed to identify the associations of target lesion restenosis following DEB use over a 1-year clinical follow-up. Between November 2011 and May 2014, 246 patients were diagnosed with coronary artery ISR in our hospital. A total of 335 coronary ISR lesions were treated with DEBs. The 1-year patent coronary artery group was defined as those with negative noninvasive examinations and no clinical symptoms, or those with no angiographic restenosis. The 1-year current restenosis group was defined as those with angiographic restenosis. Clinical results were compared between 2 groups. Univariate and multivariate cox regression analyses were performed to identify the associations of target lesion restenosis following DEB use. Patients' average age was 64.96 ± 10.68 years, and 77.2% were men. Non-ST segment elevation myocardial infarction was more frequent as the clinical presentation in the 1-year current restenosis group, whereas stable angina was more frequent in the 1-year patent coronary artery group. The 1-year current restenosis group exhibited higher percentages of comorbidities, including hypertension, diabetes, prior myocardial infarction, heart failure, prior coronary artery bypass grafting, and end-stage renal disease (ESRD). Regardless of ostial ISR or nonostial ISR, the results of drug-eluting stent ISR were worse than those for bare-metal stent ISR. Multivariate analysis revealed that ESRD, and coronary ostial lesion, and the severity of pre-PCI stenosis were independently associated with target lesion restenosis following DEB use ( P  = 0.020, P  = 0.009, P  = 0.026, respectively). ESRD, and coronary ostial lesion, and the severity of pre-PCI stenosis were independently associated with recurrent target lesion restenosis following DEB use.